Menciptakan Ruang Terbuka Hijau dengan Persepsi Keamanan sebagai Elemen Inklusif - Rahmahdini, I; Anggara, A; Margareth Aror, S (Archvisual: Jurnal Arsitektur dan Perencanaan, 2024)
Various solutions to urban problems caused by increased urbanisation have been tried, including a sustainable development strategy. Point 11 of the Sustainable Development Goals calls for urban development to focus on creating inclusive, safe, resilient, and sustainable settings. Green open space is a vital urban environment for people's lives, and providing it does not mean sacrificing inclusive aims, such as establishing safe and sustainable spaces. This research aims to find a common ground between how to plan the provision of inclusive urban green spaces and enhance its users' safety perception. This study employed a comprehensive literature review approach. The collected literature is based on commonalities in study objectives, and the outcomes are compared to conclude this research. According to the literature review results, inclusive and safe public places are connected concepts. Designing security facilities in green open spaces can help to improve inclusion. Furthermore, developing safe green open spaces indirectly improves the space's social performance, creating inclusive green spaces.